2008
DOI: 10.3354/dao01946
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Lepeophtheirus salmonis larval abundance in a sea loch on the west coast of Scotland between 2002 and 2006

Abstract: A survey for planktonic sea louse larvae was carried out in Loch Shieldaig, Scotland, between 2002 and2006, and spanned 2 successive production cycles (Cycles 1 and 2) at a local Atlantic salmon Salmo salar L. farm. The vast majority of the caligid copepodids recovered were Lepeophtheirus salmonis; however, the methodology was unable to determine the species of the caligid nauplii. Greatest densities of nauplii were found at the sampling station adjacent to the salmon farm, and larval densities were low durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 43 publications
5
11
0
Order By: Relevance
“…These results are consistent with Penston et al (2008b) and Penston & Davies (2009), who found significant correlations between L. salmonis copepodid densities in the water column and gravid lice counts on nearby farms. However, when the de-trended data were examined, there was no evidence that directed changes in counts at the farms, brought about through treatment events, led directly to changes in infestation pressure at the sentinel cages.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are consistent with Penston et al (2008b) and Penston & Davies (2009), who found significant correlations between L. salmonis copepodid densities in the water column and gravid lice counts on nearby farms. However, when the de-trended data were examined, there was no evidence that directed changes in counts at the farms, brought about through treatment events, led directly to changes in infestation pressure at the sentinel cages.…”
Section: Discussionsupporting
confidence: 91%
“…1), and given the low number of returning salmonids in the Torridon system (Penston et al 2008b), it is probable that the numbers of gravid lice on the fish farms were the dominant drivers of infestation pressure at the sentinel cages. Formally, however, the data provide no evidence of causality, only of association.…”
Section: Discussionmentioning
confidence: 99%
“…Costelloe et al (1996) also found a similar pattern with samples collected closer to an Atlantic salmon farm having a greater proportion of nauplii to copepodids than samples collected distant from that farm. The ratios presented in the present study are consistent with those seen previously in this area; higher close to the farms and lower at stations further away from them (Penston et al 2004(Penston et al , 2008b. This consistency in the pattern observed using this nauplius fraction over time and space supports its wider application as an index of proximity to sources of lice.…”
Section: Discussionsupporting
confidence: 81%
“…In the Loch Torridon system between the production cycles of 2002-2003 and 2004-2005 (the latter spanning the present Cycle 1), a significant decrease in the densities of Lepeophtheirus salmonis larvae was described by Penston et al (2008b). This decrease was attributed to applications of ema mectin benzoate at Farm 1.…”
Section: Discussionmentioning
confidence: 88%
“…In the Broughton Archipelago, the abundance of lice on wild juvenile salmon was markedly reduced in 2006 (Jones & Hargreaves 2009) relative to 2004 (Jones & Hargreaves 2007), indicating treatment on farms may extend to reductions of lice in the surrounding environment. These findings are consistent with reductions in naupliar and copepodid stages of lice in plankton samples near salmon farms following treatment in Scotland (Penston et al 2008) and British Columbia (Morton et al 2010). Given the 1 to 3 mo timescale of delousing salmon farms we have estimated and the beginning of the juvenile salmon outmigration in this area in March (M. Krkošek pers.…”
Section: Discussionsupporting
confidence: 79%